Study the Expression of Tumor Growth Factor β (TGF β) in Mice Organs after Exposure to Aflatoxin B1 using Immunohistochemistry Technique - Nada H. A. L. Al-Mudallal (Journal of Global Pharma Technology, 2016)
Background: Aflatoxin B1(AFB1) had high toxicity and carcinogenecity effects on human and animals tissues and capable of affecting both the cellular and humoral immune responses resulting in impairments in cellular immunity hence decreasing the host resistance to infections. Objectives: The current study aimed to evaluate the effects of purified aflatoxine B1 on the expression of TGF β in liver, spleen and kidney of experimental mice and estimate it's concentration by using immunohistochemistry IHC technique. Methodology: Mature Swiss albino mice (male) were used in this study, animal were provided from the National Centre for Drug Control and Research /Baghdad. To study the expression of Transforming growth factor beta (TGF-β) in mice, sixteen mice (divided into four groups) were orally admenestred with (9mg/k.g.b.w., 6mg/k.g.b.w. and 3mg/k.g.b.w.) of purified aflatoxin B1 (isolated and extracted from Aspergillus flavus ) with control group (without any treatments) and the mice of each group were sacrificed after two weeks. The blood samples of the mice were collected and samples from liver, kidney and spleen were dissected out from each mouse. The expression of TGF β in these organs was estimated using immunohistochemical technique.  Results: Immunohistochemistry technique revealed that an increase in the expression of TGF β in mice liver, kidney and spleen in comparison with control group. The concentration of TGF β increased with the increase in the concentrations of purified AFB1 that had been given to the treated mice. The highest expression and concentrations of TGF β were investigated in liver, spleen and kidney respectively after treated the mice with 9m.g. /b.w. (90%) concentration of purified AFB1 which represented the affected toxic dose of this toxin. AFB1 at concentrations 6m.g/b.w. (60%) and 3m.g/b.w. (30%) also increased the expression of TGF β but lesser than (90%).Conclusion This study can be concluded that purified aflatoxin B1 (9mg/k.g, 6mg/k.g and 3mg/k.g) which represented (90%, 60% and 30%) concentrations respectively were elevated the expression of TGF-β of mice tissues that treated with these concentrations after comparison with the control. The expression of TGF-β in mice organs increased with the increased in the concentrations of purified aflatoxin B1 using immunohistochemistry technique. AFB1 90% concentrations represented the affected toxic dose and had the highest effectiveness onto the expression of TGF-β in mice organs (liver, spleen and kidney) after treated with this aflatoxin and the highest expression of TGF-β was noticed in liver, spleen and kidney respectively.  Further investigations are required to evaluate the acute and /or chronic effect of aflatoxin B1 on other cytokines expression with determining the histopathological studies of acute and /or chronic effect of aflatoxin on other organs such as lung,muscles, heart, brain, spleen and intestine are required.Keywords: TGF-β3, Gliotoxin, immunohistochemical technique